Integrated, FPGA Based NMR Teslameter and power supply for accelerator magnets - Taylor, John-Philip (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--Stellenbosch University, 2007.